Memahami Pengalaman Literasi Media Guru PAUD Studi Kasus pada Gugus Matahari Kecamatan Bandungan, Kabupaten Semarang - Retno Manuhoro Setyowati (Master of Communication Science Program, Universitas Diponegoro, 2013)
Abstract :The aims of this research are to show the experience of the teachers in understanding media literacy and to describe about the problems faced by the teachers in teaching process so that they can understand the important aspects relate to media literacy concurrently. The subjects of this research are the teachers of early childhood education and kindergarten joined in Matahari cluster in Bandungan subdistrict.The result of this research shows that the teachers knowledge about mass media that is got naturally becomes personal locus which is relevant to the active audience. Eventhough the structure of the knowledge and skill is not comprehensive, but from the teachers personal locus, it can be built a media literacy that involve teachers, parents and the environtments.Keywords: media literacy, early childhood education (PAUD) teachers, parental mediation, society empowerment.Abstraksi :Tujuan penelitian ini adalah untuk menggambarkan pengalaman para guru dalam memahami literasi media sekaligus mendeskripsikan kendala serta tantangan para guru dalam proses belajar mengajar sehingga dapat mengetahui aspek-aspek penting terkait dengan praktek literasi media. Subyek penelitian ini adalah guru-guru PAUD dan TK yang tergabung dalam Gugus Matahari,di Kecamatan Bandungan.Hasil penelitian menunjukkan bekal pengetahuan guru tentang media massa yang didapat secara natural merupakan lokus personal yang relevan dengan pengandaian khalayak aktif.Meski struktur pengetahuan dan skill tidak lengkap, namun dari lokus personal guru dapat dikembangkan sebuah bangunan pemberdayaan literasi media dengan melibatkan guru, orang tua dan lingkungannya.Kata Kunci: literasi media, guru PAUD, pendampingan, pemberdayaan masyarakat